2022
DOI: 10.3390/en15031108
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of the Information Gap Problem in Industry 4.0 Projects as a Way to Reduce Energy Consumption by the Industrial Sector

Abstract: Reducing energy consumption should be treated as crucial for contemporary information and communication technology (ICT) projects under conditions of Industry 4.0. This research proposes a wider look at the factors influencing the success of ICT industry projects, considering not only technological and procedural conditions or implementation methods but also information and competency resources, thus allowing for correct decisions to be taken during project implementation. The article analyzes the information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 49 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…In an article by Wachnik et al [16], the problem of the information gap in reducing the energy consumption in the industry, due to Industry 4.0 technologies diffusion, is considered. The authors advocate an absolute sense of the success of energy reduction industry-specific projects, associated with the development of IT, allowing for the optimization of decisions in the design of energy systems.…”
mentioning
confidence: 99%
“…In an article by Wachnik et al [16], the problem of the information gap in reducing the energy consumption in the industry, due to Industry 4.0 technologies diffusion, is considered. The authors advocate an absolute sense of the success of energy reduction industry-specific projects, associated with the development of IT, allowing for the optimization of decisions in the design of energy systems.…”
mentioning
confidence: 99%
“…In contrast to Maggiore et al (2021), Morelli et al (2022), Wachnik et al (2022), andZaidan et al (2022), it was justified that, in order to take advantage of the use of advanced technologies of Industry 4.0 in the energy economy, it is advisable to actively use them only in entrepreneurship, while their use in society and the state does not provide advantages with the current approach to the development of the energy economy based on Industry 4.0 technologies. The reasoning of this conclusion is based on the revealed absence of a positive contribution of the government AI Readiness Index to the sustainability of energy.…”
Section: Discussionmentioning
confidence: 99%
“…In the works of Amir et al (2022), Chen et al (2022), Favi et al (2022), and Vlasov et al (2019, the use of advanced Industry 4.0 technologies in the energy economy provides advantages in both production and distribution processes. Maggiore et al (2021), Morelli et al (2022), Wachnik et al (2022), andZaidan et al (2022) indicated that, in order to fully take benefit of the advanced technologies of Industry 4.0 in the energy economy, it is advisable to actively use them by representatives of all interested parties: energy companies, state regulators of the energy economy, and energy consumers. Baxter (2012), Inshakov et al (2019), Kabeyi and Olanrewaju (2022), Kapitonov et al (2019), Kluczek et al (2021), andRatner et al (2022) stated that the digitalization of the energy economy based on advanced technologies of Industry 4.0 is universal-it is suitable for all countries, regardless of their energy efficiency, role, and position in global energy markets.…”
Section: Digital Energetics Based On the Technologies Of Industry 40:...mentioning
confidence: 99%
See 1 more Smart Citation
“…The first gap is the contradiction of decarbonization as a catalyst for sustainable development while also an obstacle to economic growth. The second gap is that while the existing literature by Favi et al (2022), Mastrocinque et al (2022), Matsunaga et al (2022), Morelli et al (2022), Vitiello et al (2022), Wachnik et al (2022) points out the special context of energy development that has formed at present in the context of the AI economy, this context has been left out of consideration in decarbonization planning.…”
Section: Theoretical Mechanism and Hypothesis Built-upmentioning
confidence: 99%